Trustworthy Research Institutions: The Challenging Case of Studying theGenetics of Intelligence - Johnston, Josephine (The Hastings Center report, 2015)
It is simple enough to claim that academic research institutions ought to be trustworthy. Building the culture and taking the steps necessary to earn and preserve institutional trust are, however, complex processes. The experience motivating this special report—a request for the Center for Talented Youth at Johns Hopkins University to collaborate on research regarding the genetics of intelligence—illustrates how ensuring institutional trustworthiness can be in tension with a commitment to fostering research. In this essay, we explore the historical context for biomedical research institutions like Johns Hopkins that have worked to build local community trust. In so doing, we consider how the example under focus in this special report can lead to greater consideration of how research institutions balance fostering trust with their other commitments.